Hipocampal hormone receptors expression in late pregnant and lactating rats: effect of mild hyperthyroidism - Neira, Flavia Judith (2019)
Thyroid disorders are associated with anxiety, depression and disturb responses to stress. The effect of stress is associated with functional changes in hippocampus (HpC) and hypothalamus by activating the hypothalamichypophysis-adrenal axis (HHA) and glucocorticoid release induced to stress. This response is physiologically attenuated during lactation. We found that mild hyperthyroidism (HyperT) increases stress-induced serum prolactin (PRL) and corticosterone secretion in lactating rats suggesting that HHA remains activated in lactation. To explore possible causes of this effect we studied the expression of thyroid receptors (TR), the long isoform of PRL receptor (PRLRl), members of the PRL signaling pathway, estradiol receptor (ER) and glucocorticoid receptor (GR) in HpC of Wistar female rats in different reproductive states (day 19 of gestation (G19), 2 (L2, early lactation) and 12 (L12) of lactation) in control (Co) and HyperT rats. Mild HyperT was induced with T4 (0.1 mg/kg/day, s.c.), a dose that allows the maintenance of lactation. HpC mRNA was obtained and the expression of receptors TRa1, TRa2, TRb1, TRb2, ERa, GR and PRLRl and members of the PRL signaling pathway (STAT5b, SOCS1 and SOCS3) was determined by RTqPCR. HpC mRNA content of TRs, STAT5b (activator of PRL signaling) and SOCS1 (supressor of PRL signaling) decreased from G19 to L12 in Co and HyperT rats (p<0.05). HyperT induced increases of TRa2 (P< 0.05 vs Co) and TRb2 in L2 (p< 0.01 vs. Co) without changes in others isoforms. HyperT increased STAT5b in G19 (p<0.05 vs. Co). ERa and PRLR mRNAs were unchanged by treatment or reproductive state while GR increased in L12 in both groups (p<0.05 vs. G19).These results indicate a physiological decline in HpC responsiveness to thyroid and PRL hormones in the transition from pregnancy to lactation in Co, while the increases observed in TRa2, TRb2 and STAT5b described in HyperT rats may be involved in the persistence of high HHA axis reactivity.